PENGARUH LIVE STREAMING, CONTENT MARKETING, DAN BRAND AMBASSADOR TERHADAP KEPUTUSAN PEMBELIAN PRODUK KAHF PADA PLATFROM TIKTOK - Miftahul Huda; Septyan Budy Cahya (Jurnal Pendidikan Tata Niaga (JPTN), 2026)
This study aims to examine the extent to which Live Streaming, Content Marketing, and Brand Ambassadors can influence consumer decisions in purchasing Kahf products through the TikTok platform. The background of this research is based on the increasing role of social media as a digital marketing tool, as well as the intense competition that occurs in the male grooming industry. These conditions encourage business actors to optimize various digital-based marketing strategies to attract consumer interest. Quantitative research is the approach implemented by this study. The analysis findings demonstrate that purchasing decisions receive a significant positive influence from three variables, namely Live Streaming, Content Marketing, and Brand Ambassadors, both individually (partially) and together (simultaneously). These findings indicate that consumer trust and confidence in Kahf products can be effectively increased by delivering interesting product information through live broadcasts, presenting quality and relevant content, and using Brand Ambassadors with a high level of credibility, thus encouraging purchasing decisions. In this regard, consumer purchasing decisions on the TikTok platform can be improved by the important role of optimizing Live Streaming, Content Marketing, and Brand Ambassador strategies.